Dominica : Use of Fund Resources; Request for Emergency Assistance; Staff Report; and Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2008)
Dominica was struck by Hurricane Dean during August 16-17, 2007. A recent earthquake also underscores the vulnerability of the economy to natural disasters. Output growth slowed during the first half of 2007 as tourist arrivals stagnated across the region. Inflation was 3 1\2 percent in July, reflecting higher energy and imported food prices. Structural reforms have continued after the expiration of the poverty reduction growth facility (PRGF) arrangement. The fiscal impact of the hurricane would be largely on the expenditure side.